Special paperStent implantation into intracranial part of internal carotid artery in a patient with recurrent stroke, atrial fibrillation and iatrogenic bleeding during anticoagulant therapy - Lasek-Bal, Anetta; Ziaja, Damian; Ziaja, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Cardiovascular diseases are the leading cause of stroke. We present a 45-year-old woman with left hemisphere stroke, in which two sources of cerebral embolism were detected: atrial fibrillation and stenosis of intracranial part of left internal carotid artery. Oral anticoagulant therapy was used. The patient was qualified for intracranial revascularization. During anticoagulant therapy iatrogenic bleeding and then left hemisphere stroke occurred. Ultimately, the stent was implanted into the intracranial part of the internal carotid artery. Due to atrial fibrillation the patient is qualified for percutaneous closure of the left atrial appendage.